2004
DOI: 10.6090/jarq.38.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Complex Organic Extracts on Plantlet Regeneration from PLBs and Plantlet Growth in the Doritaenopsis Orchid

Abstract: Potato extract (PE), corn extract (CE) and papaya extract (PAE) significantly enhanced plantlet regeneration from PLBs (protocorm-like bodies) when 50 mL L ) of extract in the medium inhibited the growth of the plantlets. Among these extracts, PE at 100 mL L -1showed the optimum effect on the acceleration of shoot growth while CE at the same concentration was optimum for root growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…The addition of organic additives to the culture medium to promote in vitro growth and proliferation of orchid is a common practice (Arditti and Ernst 1993;Ichihashi and Islam 1999;Chai et al 2002;Islam et al 2003;Rahman et al 2004;Arditti 2008, George et al 2008. The presence of organic additives may contribute toward the development of a simple and economical plant culture media and at the same time minimize the used of exogenous PGRs, thereby possibly reducing the occurrence of undesired somaclonal variation (Lee and Phillips 1988;Islam et al 2003).…”
Section: Proliferation Of Secondary Plbsmentioning
confidence: 98%
“…The addition of organic additives to the culture medium to promote in vitro growth and proliferation of orchid is a common practice (Arditti and Ernst 1993;Ichihashi and Islam 1999;Chai et al 2002;Islam et al 2003;Rahman et al 2004;Arditti 2008, George et al 2008. The presence of organic additives may contribute toward the development of a simple and economical plant culture media and at the same time minimize the used of exogenous PGRs, thereby possibly reducing the occurrence of undesired somaclonal variation (Lee and Phillips 1988;Islam et al 2003).…”
Section: Proliferation Of Secondary Plbsmentioning
confidence: 98%
“…Orange juice, a complex organic extract used in this study contained carbohydrates, protein, several vitamins, lower levels of some amino acids and organic acids [31]. Any of the aforementioned components or other(s) yet unknown substances, alone or in combination might be a factor(s) enhancing plantlet regeneration compared to the control [31]. The present study revealed that 10% -15% orange juice concentrations in the MS media were more suitable for in vitro regeneration and multiplication of cocoyam plantlets.…”
Section: Resultsmentioning
confidence: 99%
“…2). Previous studies (Rahman et al 2004) reported that the germination rate of orchid species in vitro is significantly influenced by basal medium used. In this study, the effects of three different basal media on seed germination of Phalaenopsis showed the highest (83.4%) and lowest germination rate (9.4%) on Chen and half MS medium, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%